2016
DOI: 10.1038/ncomms10432
|View full text |Cite
|
Sign up to set email alerts
|

In vivo covalent cross-linking of photon-converted rare-earth nanostructures for tumour localization and theranostics

Abstract: The development of precision nanomedicines to direct nanostructure-based reagents into tumour-targeted areas remains a critical challenge in clinics. Chemical reaction-mediated localization in response to tumour environmental perturbations offers promising opportunities for rational design of effective nano-theranostics. Here, we present a unique microenvironment-sensitive strategy for localization of peptide-premodified upconversion nanocrystals (UCNs) within tumour areas. Upon tumour-specific cathepsin prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
236
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 399 publications
(239 citation statements)
references
References 45 publications
2
236
0
1
Order By: Relevance
“…Importantly, our PET imaging studies showed that GSH-NFP could eventually saturate the entire tumor over time. Unlike other stimuli-responsive organic and inorganic nanocarriers designed to aggregate at the tumor microenvironment to improve the retention on site and play the role of drug-delivery depots, [39] our NFPs can structurally evolve into more than ten times larger interfibril networks via tumor-associated protease activation to prolong local retention for weeks. Overall, the unique combination of tumor uptake, penetration, infiltration, residing, and retention properties confer great potential on advanced GSH-NFP as a carrier of chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our PET imaging studies showed that GSH-NFP could eventually saturate the entire tumor over time. Unlike other stimuli-responsive organic and inorganic nanocarriers designed to aggregate at the tumor microenvironment to improve the retention on site and play the role of drug-delivery depots, [39] our NFPs can structurally evolve into more than ten times larger interfibril networks via tumor-associated protease activation to prolong local retention for weeks. Overall, the unique combination of tumor uptake, penetration, infiltration, residing, and retention properties confer great potential on advanced GSH-NFP as a carrier of chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…To monitor the PTT efficiency, the tumor volumes were measured every other day for 2 weeks ( 39 , 40 ). The following equation was used to monitor the volume change of tumors: tumor volume = length × width 2 /2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, inorganic nanocarriers could provide multifunctional platforms for cancer treatment, such as hyperthermia therapy,67, 68 which demonstrated potential to reverse MDR in cancers by combination with chemotherapy 69. More importantly, these inorganic nanocarriers could also provide molecular imaging function, which could help monitoring drug delivery processes and therapeutic outcomes, leading to improved treatment efficacy, especially for treating MDR cancers 70, 71…”
Section: Inorganic Nanocarriers Overcoming Drug Resistance For Cancermentioning
confidence: 99%